Lag-time measurement of antioxidant capacity using myoglobin and 2,2'- azino-bis(3-ethylbenzthiazoline-6-sulfonic acid): Rationale, application, and limitation - Yu, T.-W. (2012)
10.1006/abio.1999.4314